Innovative pre-treatment techniques to prevent corrosion of metallic surfaces - Fedrizzi, L.; Terryn, H.; Simões, A. (Woodhead Publishing in materials., 2007)
There has long been a need for effective pre-treatment techniques to prevent corrosion of metallic surfaces. This important volume discusses key research on the development of pre-treatment techniques for a range of metals. Chapters review various coatings and preparation methods for aluminium and aluminium alloys such as silane films, sol-gel coatings and magnesium-rich primers. Further chapters discuss the pre-treatment methods for steel, copper and magnesium alloys. The book also assesses methods for monitoring the effectiveness of pre-treatments, covering dissolution-precipitation mechanisms and their electrochemical behaviour. Innovative pre-treatment techniques to prevent corrosion of metallic surfaces is a valuable reference for all those concerned with corrosion problems and the use of pre-treatment techniques in the coatings industry. Reviews coating and preparation methods for alluminium alloysAn authoritative overview of pre-treatments for steel, copper, zinc and magnesium alloys.